Para-s/cite, Part II. The Paracite - Constantine Nakassis (Semiotic Review)
Part II of this two-part essay continues part I’s discussion of the parasite and the citation. This essay explores the paracite, that act alongside and beyond citation, a citational act which splits and doubles itself, as citational and yet not-quite citational. Paracitations perforate and exceed the semiotic enclosure of the citation, its play on sameness and difference, identity and alterity. To explore the semiotics of the paracite I discuss Tamil youth’s engagements with (“counterfeit”) global brand garments. In conclusion I suggest that ethnography affords avenues of exploration of these paracites and the performativities they make possible in ways that other methodologies may foreclose.